Allovalency observed by transferred NOE: interactions of sulfated tyrosine residues in the N‐terminal segment of CCR5 with the CCL5 chemokine. (8th September 2020) - Kessler, Naama; Akabayov, Sabine R.; Moseri, Adi; Cohen, Leah S.; Sakhapov, Damir; Bolton, David; Fridman, Brandon; Kay, Lewis E.; Naider, Fred; Anglister, Jacob
Abstract : The N‐terminal segment of the chemokine receptor Human CC chemokine receptor 5 (CCR5), Nt‐CCR5, contains four tyrosine residues, Y3, Y10, Y14, and Y15. Sulfation of at least two of these tyrosine residues was found to be essential for high‐affinity binding of CCR5 to its chemokine ligands. Here, we show that among the monosulfated Nt‐CCR5(8‐20) peptide surrogates (sNt‐CCR5) those sulfated at Y15 and Y14 have the highest affinity for the CC chemokine ligand 5 (CCL5) chemokine in comparison with monosulfation at position Y10. Sulfation at Y3 was not investigated. A peptide sulfated at both Y14 and Y15 has the highest affinity for CCL5 by up to a factor of 3, in comparison with the other disulfated (sNt‐CCR5) peptides. Chemical shift perturbation analysis and transferred nuclear Overhauser effect measurements indicate that the sulfated tyrosine residues interact with the same CCL5‐binding pocket and that each of the sulfated tyrosines at positions 10, 14, and 15 can occupy individually the binding site on CCL5 in a similar manner, although with somewhat different affinity, suggesting the possibility of allovalency in sulfated Nt‐CCR5 peptides. The affinity of the disulfated peptides to CCL5 could be increased by this allovalency and by stronger electrostatic interactions. Abstract : Sulfation of tyrosine 10, 14 and 15 in the intrinsically disordered N‐terminal segment of the CCR5 chemokine receptor, considerably increases its binding affinity to the CCL5 chemokine. Chemical shift perturbation analysis and TRNOE measurements indicate that each of these sulfated tyrosines can individually occupy the same binding pocket of CCL5 and in a similar manner, suggesting a binding mechanism involving allovalency.